EFFECTIVENESS OF CIVIL PROTECTION UNIT POLICY IMPLEMENTATION IN MANAGING PUBLIC ORDER AND SECURITY IN THE 2024 BANDUNG ELECTIONS - Aser, Florianus; Supriatna, Dadang; Jamil, Nurul Mutmainnah; Rukmana, Maris (Department of Government, FISIP, Universitas Padjadjaran, 2025)
This study aims to evaluate the effectiveness of the policy implementation regarding the assignment of the Civil Protection Unit (Satlinmas) in maintaining order, peace, and security during the 2024 Simultaneous General Elections. The research focuses on identifying the roles, recruitment mechanisms, capacity building efforts, and implementation challenges encountered in deploying Satlinmas as Order Officers at polling stations (TPS). A qualitative approach was employed, utilizing data collection techniques such as document analysis, interviews, and field observations. Bandung City was selected as the research site due to its dynamic Satlinmas involvement during the elections. The findings indicate that despite clear regulations concerning the role of Satlinmas, several implementation gaps persist in recruitment, training, and the distribution of personnel across polling stations. The lack of synergy among Satpol PP, Linmas Task Force, and the National Unity and Politics Agency (Kesbangpol), along with limited budget allocation, was identified as a significant obstacle in optimizing the function of Satlinmas. These findings underscore the need for a more effective policy reformulation in assigning and empowering Satlinmas. The study recommends continuous training programs, enhanced inter-agency coordination, and adequate budget provision to support the effective role of Satlinmas in ensuring safe and orderly elections.gb777